ANALISIS PERILAKU MASYARAKAT PASAR MENGENAI PENGGUNAAN RODENTISIDA DAN DAMPAKNYA TERHADAP KUCING LIAR - Nurul Fadhilatunnisa; Sudarti Sudarti; Wachju Subchan (Jurnal Kesehatan Masyarakat dan Lingkungan Hidup, 2021)
Inappropriate use of rodenticides by most market communities has resulted in a reduction in the population of feral cats (Felis catus) found in the market. If this continues, it can lead to the extinction of feral cat species in the area. This study aims to describe the level of knowledge and attitudes of the market community regarding the use of rodenticides and their impact on feral cats (Felis catus). This study used a survey method, namely interviews and observations of 28 respondents who claimed to have used rodenticides. The results showed that 35.7% of respondents had a low level of knowledge, 39.3% had a moderate level of knowledge, and 25% had a high level of knowledge. As for the attitude aspect, the majority of the community obtained quite good criteria with an average of 68.